2019
DOI: 10.3390/universe5050131
|View full text |Cite
|
Sign up to set email alerts
|

Slim Accretion Disks: Theory and Observational Consequences

Bozena Czerny

Abstract: Slim accretion disks idea emerged over 30 years ago as an answer to several unsolved problems. Since that time there was a tremendous increase in the amount of observational data where this model applies. However, many critical issues on the theoretical side remain unsolved, as they are inherently difficult. This is the issue of the disk stability under the radiation pressure, the role of the magnetic field in the energy transfer inside the disk and the formation (or not) of a warm corona, and outflows. Thus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 75 publications
0
13
0
1
Order By: Relevance
“…This model has frequently been applied to explain short-time spectral changes in type 1 Seyfert galaxies by changes in the location and geometry of the corona. Third, on longer timescales, changes in the accretion rate including disk instabilities can cause high or low states in AGN (e.g., Ross et al 2018;Czerny 2019). This last mechanism has been favored to explain some of the extreme changinglook AGN that also switch their Seyfert types.…”
Section: Discussionmentioning
confidence: 99%
“…This model has frequently been applied to explain short-time spectral changes in type 1 Seyfert galaxies by changes in the location and geometry of the corona. Third, on longer timescales, changes in the accretion rate including disk instabilities can cause high or low states in AGN (e.g., Ross et al 2018;Czerny 2019). This last mechanism has been favored to explain some of the extreme changinglook AGN that also switch their Seyfert types.…”
Section: Discussionmentioning
confidence: 99%
“…In the simplest theoretical framework, active galactic nuclei (AGN) are sources in which a supermassive black hole is surrounded by a geometrically thin, optically thick accretion disk Shakura & Sunyaev (1973). For some objects, though, modifications to accretion disk, like advection-dominated accretion flow (ADAF) or slim accretion disks (for review see Czerny 2019), are needed to better represent the observed spectra. AGN also show variability in different timescale, pattern and wavelengths like X-ray (Lawrence & Papadakis 1993), optical (Sesar et al 2007), and infrared (Kozłowski et al 2016) bands.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their extremely large optical depths, accretion disks with Ṁ ṀEdd can no longer cool efficiently. The accretion flow traps photons and the advection of radiation becomes the primary mode of energy transport in the disk (Begelman 1978;Abramowicz et al 1988;Sadowski & Narayan 2016;Czerny 2019). The large concentration of photons launches a radiation-pressuredriven outflow, which originates at the radius where the radiation flux through the surface of the disk becomes super-Eddington (Shakura & Sunyaev 1973).…”
Section: Introductionmentioning
confidence: 99%